a Arab: Depression and its Relationship with the Five Basic Human Needs in the Novel Wiṣāl Al-Rūh by Sarah Jawhar (Literary Psychological Studies) - Buana, Cahya; Hasanah, Uswatun (Diwan : Jurnal Bahasa dan Sastra Arab, 2025)
يهدف هذا البحث إلى معرفة أشكال الاكتئاب التي عانت منها الشخصية الرئيسية في رواية "وصال الروح" لسارة جوهر، بما فيه أعراضه وأسبابه وطريقة علاجه. يستخدم البحث دراسة نوعية وصفية مع مقاربة دراسة علم النفس الأدبي ونظرية التسلسل الهرمى للاحتياجات الإنسانية لأبراهام ماسلو لتحليل أسباب الاكتئاب ومعايير تشخيصي من المرشد التشخيصي الإحصائي الرابع (DSM IV-TR) لتحليل أشكال وأعراض الاكتئاب. وبعد التحليل ظهر أنّ ياسمي كالشخصية الرئيسية في رواية وصال الروح عانت من الاكتئاب الشديد. وهناك ستة أعراض تشير على ذلك وهي مزاج الاكتئاب، وفقدان الاهتمام والمتعة، والتغيرات في الشهية، والأرق، والشعور بلاجدوى والرغبة في الانتحار. وأما سبب ظهور هذه الأعراض فهو الفشل في تلبية خمسة حاجات أساسيات لديها، وهي الحاجة الفسيولوجية والحاجة إلى الأمن والآمان والحاجة إلى الحب والإنتماء والحاجة إلى تقدير الذات والحاجة إلى تحقيق الذات. تمكنت ياسمي من التغلب على هذا الاكتئاب الشديد بتلبية جميع حاجاتها الأساسية التي لم تتم تلبيتها قبله، وكان إيمانها بالله سبحانة وتعالى هو أفضل علاج جعلها ناجحة في التغلب على الاكتئاب الشديد الذي عانت منه. Abstract This study aims to reveal the type of depression experienced by the main character of the novel Wiṣāl al-Rūh by Sarah Jauhar, as well as its symptoms, causes and remedies. The research uses a descriptive qualitative method with a literary psychology approach and Abraham Maslow's psychological theory to analyze the causes of depression in the main character and diagnostic criteria from DSM IV-TR to analyze the forms and symptoms of depression in the main character. Based on the analysis, it is evident that Yāsmī, the main character of the novel Wiṣāl al-Rūh, suffers from major depression and there are six symptoms of major depression that appear in Yāsmī, namely depressed mood, loss of interest and pleasure, changes in appetite, insomnia, feelings of worthlessness, and suicidal ideation. The cause of these symptoms was due to the unfulfillment of five basic human needs in Yāsmī namely physiological needs, security needs, love and belonging needs, self-esteem needs, and self-actualization needs. Yāsmī successfully went through this severe depression with the fulfillment of all the basic needs that were previously unmet, in addition to her belief in Allah swt. is the best treatment that brought her successfully through the severe depression she suffered.